Parents in preparing meal for children: knowledge, attitude and practice / Nurul Falah Hashim ... [et al.] - Hashim, Nurul Falah; Mohd Shariff, Shazali; Yaakob, Mohd Yusof; Md Sahak, Adibah Aishah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The upbringing has the greatest influence on children's food and physical activity habits. Parents play a crucial role in moulding their children's health behaviours through their habits form in early life. Parents have a major impact on their children's eating habits and food choices. Children's poor eating habits and food choices are led to serious health consequences. In Southeast Asia, Malaysia has known as the highest obesity rate. At the same time, it is estimated that one-fifth of Malaysian children under the age of five are stunted owing to malnutrition. The study is focusing on the knowledge, attitude and practice variables among parents during preparation of children's food. The controlling of food habit, food intake, physical activities, selection of the nutritious food and food safety and sanitation from home are crucial. Thus, the participants of the study included 138 parents with children. The analyses involved descriptive statistics, Pearson's correlation and multiple regression analysis. Children learn their habits and action from the perspective of what they see through their eyes and in turn they imitate and follow the parent's practise. The huge commitment and willingness of the parents can change the future children's health, cognitive and physical.